2008
DOI: 10.1093/jn/138.8.1452
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease in Humans Is Associated with Increased Plasma Endotoxin and Plasminogen Activator Inhibitor 1 Concentrations and with Fructose Intake

Abstract: Results of animal experiments suggest that consumption of refined carbohydrates (e.g. fructose) can result in small intestinal bacterial overgrowth and increased intestinal permeability, thereby contributing to the development of nonalcoholic fatty liver disease (NAFLD). Furthermore, increased plasminogen activator inhibitor (PAI)-1 has been linked to liver damage of various etiologies (e.g. alcohol, endotoxin, nonalcoholic). The aim of the present pilot study was to compare dietary factors, endotoxin, and PAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
316
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 368 publications
(350 citation statements)
references
References 25 publications
28
316
3
1
Order By: Relevance
“…Rather, our results suggest that an increased intestinal translocation of bacterial endotoxin and subsequent activation of Kupffer cells through a TLR-4-dependent mechanism mediated through MyD88-dependent signaling pathways may also partially add or even enhance the development of this liver disease (e.g., through causing insulin resistance). These findings are also in line with results of recent human studies 6,7 suggesting that in patients with NAFLD, both dietary fructose intake and plasma endotoxin levels are elevated in comparison to controls. However, additional studies will be necessary to further explore underlying mechanisms and possible resulting therapeutic strategies (e.g., fructose avoidance therapy, treatment with antibiotics).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Rather, our results suggest that an increased intestinal translocation of bacterial endotoxin and subsequent activation of Kupffer cells through a TLR-4-dependent mechanism mediated through MyD88-dependent signaling pathways may also partially add or even enhance the development of this liver disease (e.g., through causing insulin resistance). These findings are also in line with results of recent human studies 6,7 suggesting that in patients with NAFLD, both dietary fructose intake and plasma endotoxin levels are elevated in comparison to controls. However, additional studies will be necessary to further explore underlying mechanisms and possible resulting therapeutic strategies (e.g., fructose avoidance therapy, treatment with antibiotics).…”
Section: Discussionsupporting
confidence: 91%
“…4,5 Furthermore, it has recently been shown that in patients with NAFLD (e.g., with simple steatosis and steatohepatitis with begin-ning fibrosis) intake of fructose is markedly higher than in controls. 6,7 In line with these findings it has been shown in animal studies that an increased consumption of fructose (e.g., up to 60% of daily calories derived from fructose) may result in hepatic steatosis accompanied by insulin resistance, elevated plasma triglyceride levels, and oxidative stress in the liver. [8][9][10][11] In addition, we recently showed that even the early stages of fructose-induced NAFLD (e.g., steatosis) are associated with an increased intestinal translocation of bacterial endotoxin, formation of 4-hydroxynonenal adduct formation, and expression of tumor necrosis factor alpha (TNF␣) in the liver.…”
mentioning
confidence: 61%
“…In particular, a recent work 4 demonstrates that patients with NAFLD have a significantly greater consumption of fructose than controls, and an increased hepatic expression of fructokinase messenger RNA. Although the role of TLR-4 in carbohydratedependent NAFLD has been only recently suggested by Thuy and colleagues, 5 they have pinpointed one of the potential mechanisms through which fructose could participate in NAFLD development and progression in humans: a carbohydrate-rich diet may produce ethanol when intestinal stasis favors bacterial overgrowth in the upper parts of the gastrointestinal tract. The increased portal endotoxemia could initiate TLR signaling and induce necroinflammation, which characterizes steatohepatitis, the most advanced form of NAFLD.…”
Section: Toll-like Receptor 4: a Starting Point For Proinflammatory Smentioning
confidence: 99%
“…We assessed the ability of these two indexes and of plasma cytokeratin-18 fragments (CK-18) to predict the presence of nonalcoholic fatty liver disease (NAFLD) and of nonalcoholic steatohepatitis (NASH), 1,2 respectively, and their relations to validated predictors of incident cardiovascular disease and diabetes. 3,4 To this purpose, 125 subjects (40 nondiabetic patients with biopsyproven NAFLD and 85 healthy controls) underwent an oral fat tolerance test, 5 with measurement of postprandial plasma lipid responses, and a standard oral glucose tolerance test (OGTT), whose results were elaborated by Minimal Model analysis to assess whole-body, hepatic, and muscle insulin sensitivity and indexes of pancreatic ␤-cell function (namely, CP-genic index [CGI] and Adaptation Index [AI]), as previously described. [5][6][7] Finally, circulating markers of inflammation (Creactive protein), endothelial dysfunction (E-selectin and intercellular adhesion molecule-1 [ICAM-1]) and oxidative stress (nitrotyrosine and oxidized low-density lipoproteins) were measured.…”
Section: Toll-like Receptor 4: a Starting Point For Proinflammatory Smentioning
confidence: 99%
See 1 more Smart Citation